Estimation of mass balance of Aldegondabreen (Spitsbergen) in 2015–2018 based on ArcticDEM, geodetic and glaciological measurements - A. V. Terekhov; G. V. Tarasov; O. R. Sidorova; V. E. Demidov; M. A. Anisimov; S. R. Verkulich (Лëд и снег, 2020)
The Aldegonda (Aldegondabreen) Glacier, located on the Nordenskjold Land, West Spitsbergen, covers the area of about 6  km2 (in 2018) and does constantly retreat since the very first observations of 1936. In August 2018, a topographic survey of the glacier was carried out. By comparing the results with the ArcticDEM model, built from space images of 2015, the difference in heights of the surface over three years had been calculated. Comparison of this difference with in situ data of glaciological measurements by the ablation stakes, made during the same period 2015–2018, demonstrated a high correlation between them. Considering the almost complete absence of snow cover on the glacier at the end of the summer season, the difference was recalculated into the spatial distribution of the specific mass balance by multiplying the ice density (0.88 g cm−3). Using the empirical dependence of the specific mass balance on the altitude above sea level, the obtained values were extrapolated to that part of the glacier which was not surveyed in 2018. The total loss of the Aldegonda Clacier mass for 2015–2018, calculated on the basis of topographic survey and the ArcticDEM, was estimated as 30.3 million tons (about 10.1 million tons per year). This magnitude gives the value of mean annual specific balance of approximately −1.76 m w.e, which is almost 2.5 times larger modulo than the previously published mean for the period 1936–1990, but close to the values of the early 2000s. Despite the small difference in the values obtained by geodetic and glaciological methods, the measurements does not show a systematic shift relative to each other and demonstrate approximately the same intervals of specific balance from the glacier tongue to its upper reaches (−1.08 ÷ −3.01 m w.e). This makes possible to conclude that the ArcticDEM model has the satisfactory vertical accuracy (both relative and absolute) to study on its basis changes in the surface height of an individual glacier.